(untitled) (ENTHYMEMA, 2019)
The paper deals with the relationship between educational gesture and poetic word starting from a reading of the educational experience which, when compared to the analytic experience, can be considered as a non-prefigured and prescriptive path, but as an "open" movement generative of meaning. In this research the figures of Exile and Adventure seem to be significant.